Ongoing Research on Microgreens: Nutritional Properties, Shelf-Life, Sustainable Production, Innovative Growing and Processing Approaches - Massimiliano Renna; Vito Michele Paradiso (Foods, 2020)
Microgreens garner immense potential for improving the nutritional value of the human diet, considering their high content of healthy compounds. On the other hand, they are gaining more and more interest not only for their nutritional value but also for their interesting organoleptic traits and commercial potential. The purpose of this Special Issue is to publish high-quality research papers with the aim to cover the state-of-the-art, recent progress and perspectives related to production, post-harvest, characterization, and potential of microgreens. A broad range of aspects such as cultivation, post-harvest techniques and packaging, analytical methods, nutritional value, bioaccessibily and prospects are covered. All contributions are of significant relevance and could stimulate further research in this area.